2017
DOI: 10.1001/jamapsychiatry.2017.1925
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Suicide Attempt Among Soldiers in Army Units With a History of Suicide Attempts

Abstract: Objective Soldiers’ mental health is adversely affected by the death and injury of other unit members, but it is not known if risk of suicide attempt is influenced by previous suicide attempts in one’s unit. Method Using administrative data from the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS), we identified person-month records for all active duty Regular Army enlisted soldiers who attempted suicide from 2004–2009 (n=9,650) and an equal-probability sample of control person-months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…A different study focused on suicidal thoughts and behaviors in National Guard members specifically and concluded that individuals knowing people who died by suicide were themselves at higher risk for recent suicidal thoughts (Bryan, Cerele, & Bryan, ). This is consistent with other studies that show the contagion of suicidality in military units (Hoge, Ivany, & Adler, ; Ursano et al., ). Multiple factors have been associated with the timing of postdeployment suicides among National Guard service members.…”
Section: Suicide In Military Populationssupporting
confidence: 93%
“…A different study focused on suicidal thoughts and behaviors in National Guard members specifically and concluded that individuals knowing people who died by suicide were themselves at higher risk for recent suicidal thoughts (Bryan, Cerele, & Bryan, ). This is consistent with other studies that show the contagion of suicidality in military units (Hoge, Ivany, & Adler, ; Ursano et al., ). Multiple factors have been associated with the timing of postdeployment suicides among National Guard service members.…”
Section: Suicide In Military Populationssupporting
confidence: 93%
“…Assessment of suicide risk among soldiers would benefit from awareness of recent family violence events, and recognition of the association between family violence and suicide risk should be incorporated into evidenced-based family and marital therapies. There is a need for the development of interventions specific to suicidality following family violence and, more generally, suicide-specific interventions that consider context (e.g., Ursano et al, in press). It would also be beneficial to provide education on suicide risk to workers in the legal system and social support services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, survey research indicates that exposure to suicide is associated with increased risk of suicidal thoughts and behaviors among National Guard soldiers, particularly among those who were close to the decedent (Bryan, Cerel, & Bryan, 2017). Given evidence that previous suicide attempts within an AC Army unit increases subsequent risk of attempt among unit members (Ursano, Kessler, Naifeh, Herberman Mash, Fullerton, Bliese, et al, 2017), it will be important examine this question in the RC as well.…”
Section: Discussionmentioning
confidence: 99%